2014
DOI: 10.1128/jb.01494-14
|View full text |Cite
|
Sign up to set email alerts
|

RecO and RecR Are Necessary for RecA Loading in Response to DNA Damage and Replication Fork Stress

Abstract: bRecA is central to maintaining genome integrity in bacterial cells. Despite the near-ubiquitous conservation of RecA in eubacteria, the pathways that facilitate RecA loading and repair center assembly have remained poorly understood in Bacillus subtilis. Here, we show that RecA rapidly colocalizes with the DNA polymerase complex (replisome) immediately following DNA damage or damage-independent replication fork arrest. In Escherichia coli, the RecFOR and RecBCD pathways serve to load RecA and the choice betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 64 publications
4
85
0
Order By: Relevance
“…Two pathways potentially load RecA onto DNA in B. subtilis: RecFOR at single-strand gaps or AddAB at double-strand breaks. Previous studies indicated that RecO is required for RecA localization in response to treatment with DNA-damaging agents in cells grown in minimal medium (16). However, the potential contribution of either pathway to RecA loading in cells grown in rich medium without exogenous damage is unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two pathways potentially load RecA onto DNA in B. subtilis: RecFOR at single-strand gaps or AddAB at double-strand breaks. Previous studies indicated that RecO is required for RecA localization in response to treatment with DNA-damaging agents in cells grown in minimal medium (16). However, the potential contribution of either pathway to RecA loading in cells grown in rich medium without exogenous damage is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…AddAB processes double-strand breaks to generate 3= overhangs (22). Previous work suggested that RecO is required to load RecA onto the DNA regardless of the type of damage, even at doublestrand breaks (16). These investigations used RecA-GFP focus formation as a readout for RecA loading in cells growing in minimal medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bacillus subtilis and Deinococcus radiodurans, the Rec-FOR system is the principal mediator that loads RecA onto ss-DNA. In B. subtilis, recR and recO are required for RecA focus formation on the chromosome in response to replication stress and exogenous DNA damage (17). Loss of RecF does not abolish RecA focus formation during damage but does delay the kinetics, including following a DSB produced by the homing endonuclease I-SceI (17).…”
mentioning
confidence: 99%
“…In B. subtilis, recR and recO are required for RecA focus formation on the chromosome in response to replication stress and exogenous DNA damage (17). Loss of RecF does not abolish RecA focus formation during damage but does delay the kinetics, including following a DSB produced by the homing endonuclease I-SceI (17). In contrast, all three components of the RecFOR system, in addition to RecA, are required for B. subtilis spore resistance to ionizing radiation (IR) and desiccation (18).…”
mentioning
confidence: 99%